Substance Use among Adolescents in Spain: A Brief Report - Arroyo A; Coronas C (Journal of Addiction Medicine and Therapeutic Science - Peertechz Publications, 2017)
Introduction: The consumption of alcohol and illegal drugs is a worldwide public health problem of great social impact when it affects adolescents. Aims: Evaluate the data published by offi cial statements in Spain regarding the consumption of alcohol and drugs of abuse in adolescents. Methods: the data published in Spain by STUDES (Survey on Drug Use among Secondary School Students) have been consulted. The survey is done periodically every two years. The prevalence of these consumptions as well as trends and evolution over time are shown. These data are collected from the population surveys of high school students in the fi eld of adolescence and published within the Spanish National Drug Plan throughout the country. Data were collected between 2014 -2015 and published in 2016. The emergence of consumption of new psychoactive drugs is also evaluated The alerts and controls established by the Spanish government for the detection of new synthetic drugs such as cathinones, synthetic cannabinoids and others drugs of recent appearance are stated out. Results: The prevalence of alcohol consumption in adolescent students in the last twelve months from 2012-2014 is high. These data are compared with those of other countries inside and outside the European Union. There are different trends in illicit drugs in a period between 1994 and 2014. The consumption of hypnosedatives substances increases, stable tendency of the consumption of cocaine and moderate decrease of the consumption of cannabis as well as the ecstasy, amphetamines, hallucinogens and heroine. Conclusions: the data are of interest in epidemiology and public health. Education in schools, voluntary treatment of consumers, police and customs controls and advertising campaigns are required to control and minimize this problem.